Initial investigation and the equality of the parties within the mexican criminal process - Orozco González, Wilberth; Rojas Maldonado, Natasha Ekaterina; Díaz Salazar, Valeria (Scientific journal of social studies, 2024)
It is based on the premise that equality between the parties is an essential principle of criminal procedure that seeks to guarantee a fair and equitable trial for all parties involved. Therefore, it is analyzed how this principle is fulfilled in practice, taking as an example the judicial districts VII and XII of the state of Jalisco in Mexico. To this end, a study with a qualitative approach is carried out, through the review of Mexican legislation on criminal matters and the participation of litigants and public ministries of the study area is analyzed, which shows the lack of equality between the parties in the initial research phase. It is concluded that, although the Mexican adversarial criminal system has equality between the parties as one of its fundamental principles, in practice there are inequalities in the initial investigation stage, where the defense has limitations in access to information and resources, which generates an asymmetry in the criminal process. Finally, with this study, a reform to articles 218 and 219 of the National Code of Criminal Procedures is proposed as one of the possible solutions to the problem, to achieve equality between the parties in the initial investigation stage, in which it is established clearly the scope of the rights and obligations of the defense at this stage and thus guarantee their access to the information and resources necessary for an effective defense.